MATERNAL DEATH DUE TO APLASTIC ANEMIA – A CASE REPORT - A. M. Ali, Abdelaziem; Ali, Abdalla; Karoum, Abulgasim Osman (Gezira Journal of Health Sciences, 2010)
Aplastic anaemia is characterized by a failure or suppression of multipotent myeloid stem cell resulting in pancytopenia (neutropenia, anaemia and thrombocytopenia). The cause can be inherited or acquired. The acquired causes mainly due to myelotoxic drugs and chemical, radiation and viral infection [1]. Aplastic anaemia in pegnancy is a rare disease with a major risk of materno-fetal morbidity and mortality, although the causal relationship is questioned [2].  Infections and bleeding remain the main cause of death in these patients [3]. ]. Pregnancy was suggested as a possible cause  due to suppression of hematopoiesis by placental lactogens[4]. This is supported by the clinical observation that the aplastic anaemia associated with pregnancy is frequently self-limited, ending with delivery,[5]. In places where nutritional anemia is prevalent, as in the tropics, aplastic anemia may be diagnosed late due to assumption that it is nutritional. We report a case of aplastic anaemia in pregnancy that lead to maternal death